(untitled) (Acta Scientiarum. Agronomy, 2016)
Anthracnose caused by the fungus Colletotrichum lindemuthianum is one of the main diseases affecting the common bean (Phaseolus vulgaris L.), and the pathogen is characterized by wide variability, with more than 50 physiological races identified in Brazil. Greater occurrences of races 65, 73, and 81 have been observed in Brazil along with the occurrence of pathogenic variability among isolates of a single race, destabilizing the resistance of commercial cultivars. Therefore, the aim of this study was to identify physiological races of C. lindemuthianum isolates collected in the states of São Paulo and Santa Catarina, Brazil and to test for variability among the isolates of race 65. The classification of 51 isolates resulted in the identification of 10 different physiological races: 4, 38, 55, 65, 73, 81, 83, 85, 321, and 351. Races 65 and 81 predominated, with frequencies of 37.25 and 35.29%, respectively. Regarding the isolates of race 65, wide physiological variability was evident, suggesting that a new differential set should be applied to detect the levels of variation among isolates of a single race of the pathogen.